2015
DOI: 10.1007/s00109-015-1332-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of SIRT1 in rheumatoid arthritis synovial fibroblasts

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by inflammation and destruction of synovial joints. The function of sirtuin (SIRT)1 in RA is inconclusive. In human synovial cells, SIRT1 was shown to promote cytokine production and apoptosis resistance. However, deletion of SIRT1 aggravated inflammatory arthritis in mice and increased production of pro-inflammatory cytokines in murine macrophages. In the current study, we investigated the regulation, expression, and function of SIRT1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…It has been argued SIRT1 aggravates inflammation by upregulating the expressions of pro-inflammatory cytokines in synovial fibroblasts ( 19 ) and in the synovial tissues of smokers with RA ( 35 ). Nevertheless, Wendling et al ( 17 ) have revealed that SIRT1 expression and its activity in the cytoplasm of PBMCs from RA patients are lower than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued SIRT1 aggravates inflammation by upregulating the expressions of pro-inflammatory cytokines in synovial fibroblasts ( 19 ) and in the synovial tissues of smokers with RA ( 35 ). Nevertheless, Wendling et al ( 17 ) have revealed that SIRT1 expression and its activity in the cytoplasm of PBMCs from RA patients are lower than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Silent information regulator 2 homolog1 (SIRT1), a NAD-dependent histone deacetylase, is involved in the pathogenesis of cancer [ 24 ], metabolic disease [ 25 ], inflammation [ 26 ] and arthritis [ 27 ]. The roles of SIRT1 in RA are mainly focused on the immune response [ 4 6 ], the proliferation and adhesion of RA FLSs [ 7 ]. To the best of our knowledge, there are no reports concerning the effect of SIRT1 on FLS invasion and joint destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, myeloid deletion of SIRT1 inhibited dendritic cell maturation and further alleviated arthritis in collagen-induced arthritis (CIA) mice [ 6 ]. In addition, SIRT1 contributed to FLS proliferation and adhesion during RA progression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, HDAC class III enzymes showed a contradictory function in RA. For example, the levels of the NAD-dependent protein deacetylase SIRT6 are increased in the joint tissues of collagen-induced arthritis (CIA) in mice, and further studies revealed that SIRT6 overexpression attenuates the severity of arthritis by reducing both the inflammatory response and tissue destruction, whereas SIRT1 levels were increased and its overexpression contributed inflammatory cytokine production [88,89]. Finally, Pan-inhibitors against the BET protein family (acetylation readers) have anti-inflammatory and anti-destructive properties in vitro [90] and in CIA mice [91,92].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%